Effects of Embryonic Inflammation and Adolescent Psychosocial Environment on Cognition and Hippocampal Staufen in Middle-Aged Mice - Wu, Yong-Fang; Zhang, Yue-Ming; Ge, He-Hua; Ren, Chong-Yang; Zhang, Zhe-Zhe; Cao, Lei; Wang, Fang; Chen, Gui-Hai (Frontiers in Aging Neuroscience, 2020)
Accumulating evidence has indicated that embryonic inflammation could accelerate age-associated cognitive impairment, which can be attributed to dysregulation of synaptic plasticity-associated proteins, such as RNA-binding proteins (RBPs). Staufen is a double-stranded RBP that plays a critical role in the modulation of synaptic plasticity and memory. However, relatively few studies have investigated how embryonic inflammation affects cognition and neurobiology during aging, or how the adolescent psychosocial environment affects inflammation-induced remote cognitive impairment. Consequently, the aim of this study was to investigate whether these adverse factors can induce changes in Staufen expression, and whether these changes are correlated with cognitive impairment. In our study, CD-1 mice were administered lipopolysaccharides (LPS, 50 μg/kg) or an equal amount of saline (control) intraperitoneally during days 15–17 of gestation. At 2 months of age, male offspring were randomly exposed to stress (S), an enriched environment (E), or not treated (CON) and then assigned to five groups: LPS, LPS+S, LPS+E, CON, and CON+S. Mice were evaluated at 3-month-old (young) and 15-month-old (middle-aged). Cognitive function was assessed using the Morris water maze test, while Staufen expression was examined at both the protein and mRNA level using immunohistochemistry/western blotting and RNAscope technology, respectively. The results showed that the middle-aged mice had worse cognitive performance and higher Staufen expression than young mice. Embryonic inflammation induced cognitive impairment and increased Staufen expression in the middle-aged mice, whereas adolescent stress/an enriched environment would accelerated/mitigated these effects. Meanwhile, Staufen expression was closely correlated with cognitive performance. Our findings suggested embryonic inflammation can accelerate age-associated learning and memory impairments, and these effects may be related to the Staufen expression.